2012
DOI: 10.1103/physrevlett.108.096403
|View full text |Cite
|
Sign up to set email alerts
|

Chirality Waves in Two-Dimensional Magnets

Abstract: We theoretically show that moderate interaction between electrons confined to move in a plane and localized magnetic moments leads to formation of a noncoplanar magnetic state. The state is similar to the skyrmion crystal recently observed in cubic systems with the Dzyaloshinskii-Moriya interaction; however, it does not require spin-orbit interaction. The non-coplanar magnetism is accompanied by the ground-state electrical and spin currents, generated via the real-space Berry phase mechanism. We examine the st… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
53
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(57 citation statements)
references
References 28 publications
4
53
0
Order By: Relevance
“…Finally, let us comment on the competition between the multiple-Q UUDD states and multiple-Q helical states with one-dimensional stripy ChDW [25,26]. In the current study, we found that the multiple-Q UUDD state is more stable than the multiple-Q helical ones with stripy ChDW by KPM-LD numerical simulations for Q 1 = (π/2,π ).…”
Section: Summary and Concluding Remarkssupporting
confidence: 53%
See 2 more Smart Citations
“…Finally, let us comment on the competition between the multiple-Q UUDD states and multiple-Q helical states with one-dimensional stripy ChDW [25,26]. In the current study, we found that the multiple-Q UUDD state is more stable than the multiple-Q helical ones with stripy ChDW by KPM-LD numerical simulations for Q 1 = (π/2,π ).…”
Section: Summary and Concluding Remarkssupporting
confidence: 53%
“…Furthermore, they have richer superstructures in the chirality than the one-dimensional stripy ones in the previous studies [25,26]. Reflecting the distinct aspect, intriguing edge-dependent electronic structures are obtained as discussed in Sec.…”
Section: E Chirality Density Wavesmentioning
confidence: 78%
See 1 more Smart Citation
“…Skyrmion lattices have recently been observed with spatial modulations up to 0.1µm [13,14]. Chiral textures lead to an anomalous Hall effect associated with huge (∼ 10 5 T ) effective magnetic fields, as predicted in the KL model with triangular lattice [15,16] Compared to ferromagnetism, these spin-textures can be very challenging to study.…”
mentioning
confidence: 99%
“…there are multiple kinds of Heisenberg spin couplings that cannot be satisfied simultaneously. Complexity may be realized with as few as two isotropic neighbor distances, but only when the spin sites form a non-Bravais lattice, such as Kagome or Pyrochlore lattices or when the interactions are non quadratic [6,7]: rigorously, on Bravais lattices with isotropic Heisenberg quadratic couplings-at most simple coplanar spin spirals are realized [8].…”
Section: Complex Orders At Weak Couplingmentioning
confidence: 99%